الرقابة القضائية على التناسب في القرارالاداري - خليفة، وهراني; علي ،شتيوي; عبدالرحيم ،ربيحة (جامعة الوادي University of El Oued, 2025)
يعود ظهور هذا المبدأ في القضاء الإداري المصري والفرنسي إلى توسع القاضي الإداري في رقابته على القرارات الإدارية، واكتشافه أساليب حديثة عززت رقابته. وتطورت الرقابة القضائية مع ظهور نظرية الخطأ البائن ونظرية الموازنة بين المنافع والمضار في مجال نزع الملكية وغيرها. هذا بالإضافة إلى ظهور نظرية الإفراط التي يُنسب إليها الفضل في القضاء المصري، والتي حققت حضورًا ملحوظًا في توسيع نطاق سلطة القضاء الإداري على القرارات التأديبية إلى حد كبير. وفي إطار تطبيق مبدأ التناسب وإلغائه، شهد القضاء الفرنسي والمصري العديد من الأحكام القضائية التي أقرت بتوسيع نطاق رقابته على القرارات الإدارية، مما أرست سوابق قضائية محترمة. وقد انضم القضاء الإداري الجزائري إلى القضاء المصري والفرنسي، ولكن بجرأة وجرأة أقل. يعود ذلك إلى اعتبارات قد تكون سياسية في مواجهة الإدارة التي لا تزال مهيمنة على البلاد، بالإضافة إلى نقص الوعي لدى الأفراد وتصوراتهم المسبقة حول عدم جدوى القضايا التي تخص الإدارة. ومع ذلك، لا يزال القضاء الإداري الجزائري بحاجة إلى تدريب مستمر واطلاع على القضاء الإداري المقارن، بالإضافة إلى العمل التشريعي. emergence of this principle in the Egyptian and French administrative judiciary can be traced back to the administrative judge's expansion of his oversight over administrative decisions and his discovery of modern methods that strengthened his oversight. Judicial oversight developed with the emergence of the theory of manifest error and the theory of balancing benefits and harms in the areas of expropriation and other fields. This was in addition to the emergence of the theory of excess, for which the Egyptian judiciary is credited. This theory achieved a remarkable presence in extending the authority of the administrative judiciary over disciplinary decisions to a large extent. Within the framework of applying and overriding the principle of proportionality, the French and Egyptian judiciary have witnessed numerous judicial rulings that recognized the extension of the administrative judge's oversight over administrative decisions in a manner that established respectable judicial precedents. The Algerian administrative judiciary has joined the ranks of the Egyptian and French judiciary, but with less boldness and courage. This is due to considerations that may be political in confronting the administration, which still holds the upper hand in the country, in addition to the lack of awareness among individuals and their preconceived notions about the futility of cases involving the administration. Despite this, the Algerian administrative judiciary remains in need of continuous training and exposure to comparative administrative judiciary, in addition to legislative work. The judiciary is freed from the discretionary power of the administration.
ماستر قانون إداري
Keywords: الرقابة القضائية، القرار الإداري، اإلدارة، مبدأ التناسب.; Judicialoversight; administrative decision; administration; The principle of proportionality.